A review of nabilone in the treatment of chemotherapy-induced nausea and vomiting - Mark A Ware; Paul Daeninck; Vincent Maida (Dove Medical Press, 2008)
Mark A Ware1, Paul Daeninck2, Vincent Maida31Pain Center, McGill University Health Center, Montréal, Quebec, Canada; 2Pain and Symptom Clinic, CancerCare Manitoba, Winnipeg, Manitoba, Canada; 3University of Toronto, Toronto, Ontario, CanadaAbstract: Chemotherapy-induced nausea and vomiting (CINV) in cancer patients places a significant burden on patients’ function and quality of life, their families and caregivers, and healthcare providers. Despite the advances in preventing CINV, a substantial proportion of patients experience persistent nausea and vomiting. Nabilone, a cannabinoid, recently received Food and Drug Administration approval for the treatment of the nausea and vomiting in patients receiving cancer chemotherapy who fail to achieve adequate relief from conventional treatments. The cannabinoids exert antiemetic effects via agonism of cannabinoid receptors (CB1 and CB2). Clinical trials have demonstrated the benefits of nabilone in cancer chemotherapy patients. Use of the agent is optimized with judicious dosing and selection of patients.Keywords: nabilone, chemotherapy-induced nausea/vomiting, pain